AB0482 MORE THAN ONE POSITIVITY FOR ANTIPHOSPHOLIPID SYNDROME DETERMINES LONG TERM ANTIBODY PERSISTENCE. (June 2019) - Pedro, Filipa; Carreiro, Filipa; Moraes-Fontes, Maria
Abstract : Background: It is generally assumed that once Antiphospholipid syndrome (APS) is diagnosed, patients should be treated with anticoagulation (ACO), possibly for a lifetime 1 . Objectives: Our main objective was the characterization of a group of patients with primary APS, evaluation of clinical profile, presence of APS antibodies (Ab) over time, recurrent thrombotic events and treatment. Methods: Demographic and clinical features of patients with APS were identified through the Unit's database. APL significant titers were retrospectively collected, 3, 6 and 9 months, every 6 months until year 6, every year until the last follow-up. LAC and aPL Ab (anticardiolipin IgG and Beta-2 Glycoprotein 1 IgG) were considered positive or negative by DRVVT/ELISA. Comparisons were made using the Wilcoxon Rank Sum and Chi square tests, p values < 0.05 were considered statistically significant (SPSS 22). Results: 67 patients were analysed; the majority were female (n=49); mean average age of APS diagnosis was at 40[±13] y-old. Evaluation period: 2 - 20 years. 52 patients had at least one thrombotic event: 7 arterial thrombosis, 30 venous thrombosis and 8 both arterial and venous thrombotic events; 7 patients had obstetrical APS and one of these had both thrombotic and obstetrical APS; 9 had severe non-thrombotic APS manifestations. Fifty-four patients are currently under warfarin, 8 of which had a thrombotic event despite ACO. Patients could be grouped into two distinct patterns: those that became persistently antibody negative (aPL-; n=19) and those in whom the antibodies remained positive, persistently or intermittently (aPL+; n=48). The major difference between groups was the occurrence of cumulative double or triple positivity in 69% of aPL+ versus 37% in aPL- (p=0.026). There were no significant differences in age, age at diagnosis, duration of the disease and frequency/type of thrombosis, between each group (Table I ). From the group that became persistently aPL-, 3 patients suspended ACO, without any event after 2 years of follow-Up. Conclusion: Our study suggests that more than one aPL/LAC positivity is associated with antibody persistence over time. In our small series, as previously reported, ACO was safely discontinued in selected patients that become aPL-, in the absence of other risk factors for thrombotic events 2 . Regular antibodies measurements may help identify a subset of patients in whom ACO may be safely discontinued under careful observation. References: Disclosure of Interests: None declared